The impact of the state on the quality of an economic system: A cross-country analysis - Maciej Bałtowski; Piotr Kozarzewski (Center for Social and Economic Research (CASE), 2019)
The paper discusses the role of the state in shaping an economic system which is, in line with the welfare economics approach, capable of performing socially important functions and achieving socially desirable results. We describe this system through a set of indexes: the IHDI, the World Happiness Index, and the Satisfaction of Life index. The characteris-tics of the state are analyzed using a set of variables which describe both the quantitative (government size, various types of governmental expenditures, and regulatory burden) and qualitative (institutional setup and property rights protection) aspects of its functioning. The study examines the "old" and "new" member states of the European Union, the post-communist countries of Eastern Europe and Asia, and the economies of Latin America. The main conclusion of the research is that the institutional quality of the state seems to be the most important for creation of a socially effective economic system, while the level of state interventionism plays, at most, a secondary and often negligible role. Geographical differentiation is also discovered, as well as the lack of a direct correlation between the characteristics of an economic system and the subjective feeling of well-being. These re-sults may corroborate the neo-institutionalist hypothesis that noneconomic factors, such as historical, institutional, cultural, and even genetic factors, may play an important role in making the economic system capable to perform its tasks; this remains an area for future research.
Keywords: P10; D63; H11; O15; 330; economic system; economic policy; welfare economics; institutions; role of the state in the economy